The happy learner: Effects of academic boredom, burnout, and engagement - Bekker, Christiaan I.; Rothmann, Sebastiaan; Kloppers, Magdalena M. (Frontiers in Psychology, 2023)
This study aimed to investigate the impact of demographic and contextual variables on boredom in English and mathematics, and to test structural models of boredom, learner burnout, learner engagement, and life satisfaction. Using a cross-sectional survey design and employing a convenience sampling technique, 544 secondary school learners in the Sedibeng District, Gauteng, South Africa, took part in the study. The participants completed the Achievement Emotions Questionnaire – English, the Achievement Emotions Questionnaire – Mathematics, the Schoolwork Engagement Inventory, the School Burnout Inventory, and the Satisfaction with Life Scale. Latent variable modeling was used to test measurement and structural models of boredom, burnout, engagement, and life satisfaction. The indirect effects of boredom on life satisfaction were also computed. The results showed that Afrikaans as the home language, the final mark for English in the previous examination, caregivers that cannot help with English homework, and disliking the English teacher predicted boredom in English. Afrikaans as the home language, marks for mathematics in the previous examination, not having the ability to focus on schoolwork at home, and disliking the mathematics teacher predicted boredom in mathematics. Boredom in mathematics and English resulted in an increase in learner burnout and a decrease in learner engagement. Furthermore, boredom in mathematics and English indirectly affected life satisfaction via learner burnout and engagement.